2018
DOI: 10.1017/s0144686x18000806
|View full text |Cite
|
Sign up to set email alerts
|

Caught between two stools? Informal care provision and employment among welfare recipients in Germany

Abstract: In many countries, population ageing is challenging the viability of the welfare state and generating higher demands for long-term care. At the same time, increasing participation in the labour force is essential to ensuring the sustainability of the welfare state. To address the latter issue, affected countries have adopted measures to increase employment; e.g. welfare recipients in Germany are required to be available for any type of legal work. However, 7 per cent of welfare benefit recipients in Germany pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 46 publications
1
15
0
Order By: Relevance
“…The same happened for mixed forms of care, whose prevalence among older people increased from 4% to 7.2%, again with a larger increase among lower educated older people (from 6.5% to 15.2%). As elsewhere in the literature, the models used have also controlled for household income to account for any differences in access to home care services (Hohmeyer & Kopf, 2018). The education gradient remained in place even after controlling for this.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same happened for mixed forms of care, whose prevalence among older people increased from 4% to 7.2%, again with a larger increase among lower educated older people (from 6.5% to 15.2%). As elsewhere in the literature, the models used have also controlled for household income to account for any differences in access to home care services (Hohmeyer & Kopf, 2018). The education gradient remained in place even after controlling for this.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, unobserved characteristics such as personal traits, preferences and social norms may also vary across educational groups rendering some individuals more prone to provide informal care (Leigh, 2010; Nguyen & Connelly, 2017). Informal carers may self‐select into certain occupations or types of employment (e.g., part‐time), which render them less likely to remain employed when care duties arise later in their lives (Hohmeyer & Kopf, 2018). Evidence from other familialistic contexts indicates that lower educated female informal carers and their frail relatives may place a greater emphasis on informal care provision as part of intrafamily reciprocity (Conlon, Timonen, Carney, & Scharf, 2014; Timonen, Conlon, Scharf, & Carneyet, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that carers are more likely than non-carers to both be, or to become, non-employed (see, for example, Pavalko and Henderson, 2006;Lee and Tang, 2013;Gomez-Leon et al, 2019;Hohmeyer and Kopf, 2020) and reduce their working hours (see, for example, Schmitz and Westphal, 2017;Gomez-Leon et al, 2019). We extend these studies by examining whether receiving monetary transfers fuels decisions to reduce employment among unpaid carers.…”
Section: Introductionmentioning
confidence: 74%
“…Employment status was defined as being employed versus not being employed. Being employed meant paying social security contributions, which in Germany, equals average monthly earnings above €450 (€400 until 2012) (Hohmeyer and Kopf, 2020). Working hours were defined as the 'weekly contractual working hours for all positions held by the respondent at the time of the interview' (Berg et al, 2020: 45).…”
Section: Measures Dependent Variablesmentioning
confidence: 99%
“…Thus far, scholars focused on two strategies for informal caregivers to adapt their work: stopping work (including early retirement) and reducing working hours. They found that informal caregivers have a higher likelihood to do both (Gomez-Leon et al 2019, Schmitz and Westphal 2017, Van Houtven, Coe, and Skira 2013, Hohmeyer and Kopf 2020.…”
Section: Introductionmentioning
confidence: 99%